The logic of four decades of economic reform and major breakthroughs in political economy in China. Issue 1 (11th June 2019) - Hong, Yinxing
Abstract : Purpose: In the process of reform, although every landmark theoretical breakthrough is marked by the speech of the highest leadership of the Communist Party of China (CPC) or the decision of the CPC National Congress, each breakthrough is attributable to the theoretical contribution made by the academia of political economy. Notably, these theoretical breakthroughs invariably embrace innovations in the discourse system of political economy. The paper aims to discuss this issue. Design/methodology/approach: The innovations and breakthroughs thereof have led to the political economy of socialism with Chinese characteristics. Findings: The success of China's economy highlights the superiority of the socialist economic system and development path with Chinese characteristics. Originality/value: These major breakthroughs are accompanied by breakthroughs in relevant theories, which constitute a synthesis of a series of major theoretical innovations in political economics.